45. COVID-19 Vulnerability and Data Reporting in Africa: Reflections from Cameroon. (4th December 2021) - Judson, Seth D; Njabo, Kevin; Torimiro, Judith
Abstract: Background: At the beginning of the COVID-19 pandemic there were many questions about vulnerability and data reporting among African countries. We previously found that policymakers in Cameroon value region-specific risk maps for emerging diseases. Therefore, we created regional vulnerability indices for COVID-19 in Cameroon. As the pandemic grew, we aimed to compare how these predictions related to reported COVID-19 cases in Cameroon and whether additional African countries had available data to assess vulnerability for COVID-19. Methods: Using data from the Cameroon 2018 Demographic and Health Survey (DHS), we had constructed an epidemiological vulnerability index based on comorbidities potentially associated with COVID-19 severity. Similarly, we had created a healthcare access index. We then compared these indices with regional COVID-19 cases per population from weekly situation reports in Cameroon. Finally, we identified the availability of DHS data and COVID-19 reporting systems in other African countries. Vulnerability Indices for COVID-19 in Cameroon The epidemiological and healthcare access vulnerability indices constructed for Cameroon are shown along with COVID-19 cases per population. Results: Adjusting for data reporting limitations, regions in Cameroon that scored higher on the epidemiological vulnerability index were associated with greater COVID-19 cases per population. We also identified regions with mismatches between high epidemiological vulnerability and low healthcare access. COVID-19 data reporting systems varied among African countries. 29/54 (53.7%) of African countries had recurrent situation reports or online dashboards with subnational COVID-19 data in 2020. Meanwhile, 36/54 (66.7%) of African countries had DHS data reported in the last decade. Conclusion: We found that vulnerability indices could be a rapid way of identifying populations at risk for emerging diseases such as COVID-19. This method could be used in other countries that have both recent health surveys from programs such as the DHS and subnational reporting of COVID-19 cases. Indices could be useful for decision-making, but they will need to be refined with national expert input. National situation reports and online dashboards provided subnational COVID-19 data in approximately half of African countries. Therefore, increased baseline health surveys as well as expanded reporting of COVID-19 case data could inform future vulnerability assessments in other countries. Disclosures: All Authors : No reported disclosures